Pengaruh Kepuasan Kerja dan Semangat Kerja Terhadap Produktivitas Kerja Karyawan (Studi Kasus Budiman Swalayan Paritrantang) - Hidayatullah, Rezky; Candra, Delni Alek; Nefri, John (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
The purpose of this study was to determine and analyze the effect of job satisfaction and work enthusiasm on the work productivity of employees of Budiman Swalayan Paritrantang. The method of determining the number of samples using saturated sampling. The number of samples in this study were 46 people. While the types and sources of data obtained through primary data and secondary data with data collection techniques obtained from distributing questionnaires and documentation. Analysis of the data obtained using multiple linear regression and carried out with simultaneous tests and partial tests. The results obtained from the research show that the variable job satisfaction significantly affects (0.009<0.05) on work productivity in employees of Budiman Swalayan Paritrantang. Likewise, the results of the work enthusiasm variable showed a significant effect (0.001<0.05) on work productivity in Budiman Swalayan Paritrantang employees. While simultaneously job satisfaction and work enthusiasm have a significant effect on work productivity in Budiman Swalayan Paritrantang employees with an Adjusted R Square value of 0.542 or 54.2%.